The illustrated network : how TCP/IP works in a modern network / Walter Goralski - Goralski, Walter
With diagrams and screenshots, and end-of-chapter questions, this unique book presents an illustrated explanation on how TCP/IP works, using consistent examples from a working network configuration that includes servers, routers and workstations.